Cognitive Radio Sensing Using Hilbert Huang Transform - Narayanankutty, K. A.; A. Nair, Abhijith; Soori, Dilip; Pradeep, Deepak; Teja, V. Ravi; K.B., Vishnu (Scientific Research Publishing, 2010)
Vast segments of the frequency spectrum are reserved for primary (licensed) users. These legacy users often un-der-utilize their reserved spectrum thus causing bandwidth waste. The unlicensed (secondary) users can take advantage of this fact and exploit the spectral holes (vacant spectrum segments). Since spectrum occupancy is transient in nature it is imperative that the spectral holes are identified as fast as possible. To accomplish this, we propose a novel adaptive spectrum sensing procedure. This procedure scans a wideband spectrum using Hilbert Huang Transform and detects the spectral holes present in the spectrum.
Keywords: Empirical Mode Decomposition (EMD); Ensemble Empirical Mode Decomposition (EEMD); Intrinsic Mode Function (IMF); Noise Assisted Data Analysis (NADA); Cognitive Radio, Guard Band; Spectrum Sensing